Donor-acceptor substituted phenylethynyltriphenylenes – excited state intramolecular charge transfer, solvatochromic absorption and fluorescence emission - Nandy, Ritesh; Sankararaman, Sethuraman (Beilstein Journal of Organic Chemistry, 2010)
Several 2-(phenylethynyl)triphenylene derivatives bearing electron donor and acceptor substituents on the phenyl rings have been synthesized. The absorption and fluorescence emission properties of these molecules have been studied in solvents of different polarity. For a given derivative, solvent polarity had minimal effect on the absorption maxima. However, for a given solvent the absorption maxima red shifted with increasing conjugation of the substituent. The fluorescence emission of these derivatives was very sensitive to solvent polarity. In the presence of strongly electron withdrawing (–CN) and strongly electron donating (–NMe2) substituents large Stokes shifts (up to 130 nm, 7828 cm−1) were observed in DMSO. In the presence of carbonyl substituents (–COMe and –COPh), the largest Stokes shift (140 nm, 8163 cm−1) was observed in ethanol. Linear correlation was observed for the Stokes shifts in a Lippert–Mataga plot. Linear correlation of Stokes shift was also observed with ET(30) scale for protic and aprotic solvents but with different slopes. These results indicate that the fluorescence emission arises from excited state intramolecular charge transfer in these molecules where the triphenylene chromophore acts either as a donor or as an acceptor depending upon the nature of the substituent on the phenyl ring. HOMO–LUMO energy gaps have been estimated from the electrochemical and spectral data for these derivatives. The HOMO and LUMO surfaces were obtained from DFT calculations.
Keywords: charge transfer; fluorescence; solvatochromism; solvent effect; triphenylene

Principles of Fluorescence Spectroscopy - Lakowicz, J. R. (Kulwer Academic, 1999)

Fluorescence Applications in Biotechnology and the Life Sciences - Goldys, E. M. (Wiley Blackwell, 2009)

(untitled) - Giepmans, B. N. G.; Adams, S. R.; Ellisman, M. H.; Tsien, R. Y. (Science, 2006)

(untitled) - Baker, A. (Environ. Sci. Technol., 2001)

(untitled) - Loudet, A.; Burgess, K. (Chem. Rev., 2007)

(untitled) - Ulrich, G.; Ziessel, R.; Harriman, A. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kowada, T.; Yamaguchi, S.; Ohe, K. (Org. Lett., 2010)

(untitled) - Thiagarajan, V.; Ramamurthy, P.; Thirumalai, D.; Ramakrishnan, V. T. (Org. Lett., 2005)

(untitled) - Badugu, R.; Lakowicz, J. R.; Geddes, C. D. (J. Am. Chem. Soc., 2005)

(untitled) - Srikun, D.; Miller, E. W.; Domaille, D. W.; Chang, C. J. (J. Am. Chem. Soc., 2008)

(untitled) - Zhang, L.; Clark, R. J.; Zhu, L. (Chem.–Eur. J., 2008)

(untitled) - Andrew, T. L.; Swager, T. M. (J. Am. Chem. Soc., 2007)

(untitled) - Dale, T. J.; Rebek, J., Jr (J. Am. Chem. Soc., 2006)

(untitled) - Fan, L.-J.; Jones, W. E., Jr (J. Phys. Chem. B, 2006)

(untitled) - Kim, S. K.; Yoon, J. (Chem. Commun., 2002)

(untitled) - Kim, S. H.; Kim, J. S.; Park, S. M.; Chang, S.-K. (Org. Lett., 2006)

(untitled) - Jung, H. S.; Park, M.; Han, D. Y.; Kim, E.; Lee, C.; Ham, S.; Kim, J. S. (Org. Lett., 2009)

(untitled) - Lee, S. H.; Kim, S. H.; Kim, S. K.; Jung, J. H.; Kim, J. S. (J. Org. Chem., 2005)

(untitled) - Park, S. Y.; Yoon, J. H.; Hong, C. S.; Souane, R.; Kim, J. S.; Matthews, S. E.; Vicens, J. (J. Org. Chem., 2008)

(untitled) - Beinhoff, M.; Weigel, W.; Jurczok, M.; Rettig, W.; Modrakowski, C.; Brüdgam, I.; Hartl, H.; Schlüter, A. D. (Eur. J. Org. Chem., 2001)

(untitled) - Beinhoff, M.; Weigel, W.; Rettig, W.; Bruedgam, I.; Hartl, H.; Schlüter, A. D. (J. Org. Chem., 2005)

(untitled) - Techert, S.; Wiessner, A.; Schmatz, S.; Staerk, H. (J. Phys. Chem. B, 2001)
and references 2-3 cited therein

Handbook of Fluorescence Spectra of Aromatic Molecules - Berlman, I. B. (Academic Press, 1965)

(untitled) - Venkataramana, G.; Sankararaman, S. (Eur. J. Org. Chem., 2005)

(untitled) - Venkataramana, G.; Sankararaman, S. (Org. Lett., 2006)

(untitled) - Yuasa, H.; Miyagawa, N.; Izumi, T.; Nakatani, M.; Izumi, M.; Hashimoto, H. (Org. Lett., 2004)

(untitled) - Kim, S. K.; Bok, J. H.; Bartsch, R. A.; Lee, J. Y.; Kim, J. S. (Org. Lett., 2005)

(untitled) - Kim, J. S.; Quang, D. T. (Chem. Rev., 2007)

(untitled) - Strauss, J.; Daub, J. (Org. Lett., 2002)

(untitled) - Cho, H. K.; Lee, D. H.; Hong, J.-I. (Chem. Commun., 2005)

(untitled) - Yang, S.-W.; Elangovan, A.; Hwang, K.-C.; Ho, T.-I. (J. Phys. Chem. B, 2005)

(untitled) - Kim, H. M.; Lee, Y. O.; Lim, C. S.; Kim, J. S.; Cho, B. R. (J. Org. Chem., 2008)

(untitled) - Oh, J.-W.; Lee, Y. O.; Kim, T. H.; Ko, K. C.; Lee, J. Y.; Kim, H.; Kim, J. S. (Angew. Chem., Int. Ed., 2009)

(untitled) - Dobkowski, J.; Retting, W.; Waluk, J. (Phys. Chem. Chem. Phys., 2002)

(untitled) - Ji, S.; Yang, J.; Yang, Q.; Liu, S.; Chen, M.; Zhao, J. (J. Org. Chem., 2009)

(untitled) - Subuddhi, U.; Haldar, S.; Sankararaman, S.; Mishra, A. K. (Photochem. Photobiol. Sci., 2006)

(untitled) - Birks, J. B.; Christophorou, L. G. (Proc. R. Soc. London, Ser. A, 1964)

(untitled) - Ikeda, M.; Takeuchi, M.; Shinkai, S. (Chem. Commun., 2003)

(untitled) - Nandy, R.; Sankararaman, S. (Org. Biomol. Chem., 2010)

(untitled) - Praefcke, K.; Kohne, B.; Singer, D. (Angew. Chem., Int. Ed. Engl., 1990)

(untitled) - Matsumoto, H.; Kyushin, S.; Negishi, K.; Ono, Y.; Uchida, M.; Oomori, H. (Triphenylene compounds, method of manufacturing the same and organic electroluminescent devices employing the same, 2008)

(untitled) - Huang, C.-C.; Lin, Y.-C.; Lin, P.-Y.; Chen, Y.-J. (Eur. J. Org. Chem., 2006)

Principles of Fluorescence Spectroscopy - Lakowicz, J. R. (Kulwer Academic, 1999)
(See for Lippert equation and its applications.)

(untitled) - Lippert, E. V. Z. (Elektrochem., 1957)

(untitled) - Mataga, K. N.; Kaifu, Y.; Koizumi, M. (Bull. Chem. Soc. Jpn., 1956)

PC Spartan Pro, Version 1.1 (Wavefunction, Inc, 1999)

Solvents and Solvent Effects in Organic Chemistry - Reichardt, C. (Wiley-VCH, 2003)

(untitled) - Reichardt, C. (Chem. Rev., 1994)

Principles of Fluorescence Spectroscopy - Lakowicz, J. R. (Kulwer Academic, 1999)

(untitled) - Beeson, J. C.; Huston, M. E.; Pollard, D. A.; Venkatachalam, T. K.; Czarnik, A. W. (J. Fluoresc., 1993)

(untitled) - Duke, R. M.; Gunnlaugsson, T. (Tetrahedron Lett., 2007)

(untitled) - Schaefer, C. G.; Peters, K. S. (J. Am. Chem. Soc., 1980)

(untitled) - Peters, K. S.; Lee, J. (J. Phys. Chem., 1993)

(untitled) - Manring, L. E.; Peters, K. S. (J. Am. Chem. Soc., 1985)